Sacred Love - Gans, Eric Lawrence (2020)
If generative anthropology is less well known than "mimetic theory," it is not simply because the latter is easier to understand. The primary reason is that, although GA can talk about sacred "fear and trembling," it does not provoke such emotions, whereas from the first (see Chronicle 507), Girard speaks directly to the soul. Mensonge...